2022
DOI: 10.3390/ph15040457
|View full text |Cite
|
Sign up to set email alerts
|

Harpagophytum procumbens Root Extract Mediates Anti-Inflammatory Effects in Osteoarthritis Synoviocytes through CB2 Activation

Abstract: The endocannabinoid system is involved in the nociceptive and anti-inflammatory pathways, and a lowered expression of CB2 receptors has been associated with inflammatory conditions, such as osteoarthritis (OA). This suggests that CB2 modulators could be novel therapeutic tools to treat OA. In the present study, the involvement of Harpagophytum procumbens root extract, a common ingredient of nutraceuticals used to treat joint disorders, in CB2 modulation has been evaluated. Moreover, to clarify the effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 46 publications
1
9
0
Order By: Relevance
“…Synergistic effects of β-caryophyllene oxide towards sorafenib were also confirmed in a xenograft model of liver cancer [20]. More recently, we reported the potentiating effects of caryophyllane sesquiterpenes towards cannabidiol and harpagoside in hemp and devil's claw extracts, respectively [18,22].…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Synergistic effects of β-caryophyllene oxide towards sorafenib were also confirmed in a xenograft model of liver cancer [20]. More recently, we reported the potentiating effects of caryophyllane sesquiterpenes towards cannabidiol and harpagoside in hemp and devil's claw extracts, respectively [18,22].…”
Section: Introductionsupporting
confidence: 52%
“…A number of natural substances have been found to be able to synergize in vitro anticancer drugs and to resensitize cancer cells, acting as chemosensitizers [16]. Among them, β-caryophyllene and β-caryophyllene oxide, two natural sesquiterpenes with a typical caryophyllane skeleton, widely occurring in plants, especially in essential oils (e.g., clove oil, apple mint oil, and hemp essential oil), seeds (e.g., Piper nigrum L.) and rhizomes (Harpagophytum procumbens DC), were shown to possess promising chemosensitizing properties, along with pleiotropic pharmacological activities, including antioxidant, antinflammatory, genoprotective, neuroprotective, and chemopreventive ones, along with a safe toxicity profile [15,17,18]. Moreover, they were found to be able to modulate multiple cascades involved in oxidative stress, inflammation, and cell survival, such as PI3K/Akt/mTOR/S6K1, NF-kB and STAT3 [15].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown to mediate anti-Inflammatory effects in Osteoarthritis synoviocytes through cannabinoid type 2 (CB2) Activation. Harpagophytum procumbens is able to inhibit the cAMP production and mitogen-activated protein (MAP) kinase activation and to down-regulate the matrix metalloproteinase (MMP-13) production which is the hallmark of osteoarthritis [21] .…”
Section: Safetymentioning
confidence: 99%
“…Moreover, the agonism of some HPE components has been shown on endocannabinoid (CB) receptors, mainly involved in anti-nociceptive transmission. Several studies have highlighted the up-regulation of CB2 following HPE treatment in vitro [ 74 , 75 ]; while in Farpour et al in vivo study, pain reduction following HPE administration was demonstrated [ 76 ]. Its in vitro and in vivo activity is due to the major chemical constituents such as iridoid glycosides (primarily harpagoside, harpagide, and procumbide), triterpenoids, phytosterols (primarily β-sitosterol) and flavonoids such as luteolin and kaempferol [ 77 ].…”
Section: Osteoarthritis and Antioxidant Treatmentmentioning
confidence: 99%
“…Harpagoside, harpagide, and procumbide, found in the tubers of the plant, appear to be the most therapeutically important constituents. Whole-plant extracts appear to have a better therapeutic effect than those prepared from isolated parts [ 71 , 75 ].…”
Section: Osteoarthritis and Antioxidant Treatmentmentioning
confidence: 99%